2022
DOI: 10.3389/fneur.2022.938360
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota Profile in a Group of Anti-AChR Antibody–Positive Myasthenia Gravis Patients

Abstract: Myasthenia gravis (MG) is an autoimmune disorder caused by autoantibodies directed against the postsynaptic membrane at the neuromuscular junction. Perturbation of gut microbiota is thought to contribute to the development of MG, as reflected by fecal metabolomic signatures in humans, but there have been few studies on the relationship between oral microbiota profile and MG. The current study evaluated the correlation between oral microbiota composition and diversity and anti-acetylcholinereceptor (AChR) antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Though phylum Actinobacteria represents only a small percentage in the four major phyla of the gut microbiota, accumulating evidence has suggested their beneficial effects in many pathological conditions. Actinobacteria was found to be significantly decreased in the fecal sample of MG patients compared with controls in several cross-sectional studies 12,26,27 ; while the inconsistent result showing increased abundance of Actinobacteria in the saliva of MG patients 28 is expected to be attributed to the difference in distribution of intestinal and oral flora. Rinaldi et al investigated the clinical efficacy of the therapeutic administration of vital bifidobacteria in MG and suggested that this probiotic therapy improved the symptoms of the experimental autoimmune MG model and decreased serum anti-rat AChR antibody levels 29 .…”
Section: Discussionmentioning
confidence: 94%
“…Though phylum Actinobacteria represents only a small percentage in the four major phyla of the gut microbiota, accumulating evidence has suggested their beneficial effects in many pathological conditions. Actinobacteria was found to be significantly decreased in the fecal sample of MG patients compared with controls in several cross-sectional studies 12,26,27 ; while the inconsistent result showing increased abundance of Actinobacteria in the saliva of MG patients 28 is expected to be attributed to the difference in distribution of intestinal and oral flora. Rinaldi et al investigated the clinical efficacy of the therapeutic administration of vital bifidobacteria in MG and suggested that this probiotic therapy improved the symptoms of the experimental autoimmune MG model and decreased serum anti-rat AChR antibody levels 29 .…”
Section: Discussionmentioning
confidence: 94%
“…The conflicting results between oral and gut microbiota deserve further investigation. However, since the gastrointestinal tract is widely populated by different bacterial species coming from the oral cavity, microbiota analyses must consider the large variety of the gastrointestinal bacterial flora in the various tracts [ 65 ]. A final consideration should be reserved for the comparison of gut microbiota alterations between MG and other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the abundance of the phyla Firmicutes and Actinobacteria was increased in patients with MG, while Proteobacteria were the predominant phylum in healthy controls. Furthermore, they evidenced that bacteria of the genera Streptococcus , Rothia , Lachnoanaerobaculum and Oribacterium were increased in MG patients while the proportions of Neisseria , Haemophilus and Treponema were significantly decreased when compared with healthy controls [ 65 ]. Oral abundance of Firmicutes was, in contrast with their reduction in the gut microbiota, reported in other studies.…”
Section: Oral Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Another analysis revealed that MG is associated with a lower abundance of Verrucomicrobiaceae and Bifidobacteriaceae and an increased abundance of Bacteroidetes and Desulfovibrionaceae ( Moris et al, 2018 ). Specially, Huang et al found that AChR positive MG patients also experience changes in their oral microbiota ( Huang et al, 2022 ). Our study identified bacterial genera for which the abundance differed in individuals with and without MG and applied two microbiomes-based ML models to identify key bacterial taxa.…”
Section: Discussionmentioning
confidence: 99%